2016
DOI: 10.1002/cyto.a.22873
|View full text |Cite
|
Sign up to set email alerts
|

Point process models for localization and interdependence of punctate cellular structures

Abstract: Background Accurate representations of cellular organization for multiple eukaryotic cell types are required for creating predictive models of dynamic cellular function. To this end, we have previously developed the CellOrganizer platform, an open source system for generative modeling of cellular components from microscopy images. CellOrganizer models capture the inherent heterogeneity in the spatial distribution, size, and quantity of different components among a cell population. Furthermore, CellOrganizer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…To further test the possibility that the unsupervised analysis in the feature space reveals higher resolution functional information than expert annotation, we asked if our features could be used to discover higher-resolution subclasses of proteins that are difficult for experts to annotate visually. First, previous work with vesicle-localized proteins in the Human Protein Atlas has suggested that these proteins can be distinguished into many subclasses (2,51). We clustered features for human proteins annotated to localize to the vesicle only, and found structure in the feature representation that corresponds to visually-distinct vesicle patterns (Abundantly and more evenly distributed in the cytosol, concentrated closer to the nucleus or sparse puncta, Supplementary Figure 2, Clusters A, B and C respectively).…”
Section: Proteome-wide Clustering Of Human Proteins With Paired Cell mentioning
confidence: 93%
“…To further test the possibility that the unsupervised analysis in the feature space reveals higher resolution functional information than expert annotation, we asked if our features could be used to discover higher-resolution subclasses of proteins that are difficult for experts to annotate visually. First, previous work with vesicle-localized proteins in the Human Protein Atlas has suggested that these proteins can be distinguished into many subclasses (2,51). We clustered features for human proteins annotated to localize to the vesicle only, and found structure in the feature representation that corresponds to visually-distinct vesicle patterns (Abundantly and more evenly distributed in the cytosol, concentrated closer to the nucleus or sparse puncta, Supplementary Figure 2, Clusters A, B and C respectively).…”
Section: Proteome-wide Clustering Of Human Proteins With Paired Cell mentioning
confidence: 93%
“…As seen by the number of emerging studies, there is an obvious need for quantitative methods that can capture and describe complex spatial associations . The consideration of cells in tissues as point patterns enables the use of point processes statistical theory, which provides validated mathematical methods widely employed in other fields dealing with spatially organized systems .…”
Section: Spatial Analyses Of Hsc Distributions and Interactionsmentioning
confidence: 99%
“…The reason for such a difference is we focus on binary classification other than a generalized multi-categorical classification problem in this section. Table 2.1, the expected cost EC(t 1 ,t 2 ) can be formulated with thresholds t 1 and t 2 [23]: 16) where FNR , T NR, T PR, FPR are the false negative rate, the true negative rate, the true positive rate and the false positive rate while RP and RN are the rejection rates on the positive and the negative samples, respectively. p(P) and p(N) are the prior probabilities of the positive and negative classes, respectively.…”
Section: )mentioning
confidence: 99%
“…Different pairs of (P, R) determine different LBP configurations. The most typical settings are (8,1), (12,2) and (16,4) [48].…”
Section: Siftmentioning
confidence: 99%
See 1 more Smart Citation